A priority list-based fuzzy logic controller for short-term unit commitment problem. (18th September 2019) - Kumar, Jitendra; Verma, Ashu; Bhatti, T.S.
This paper presents a fuzzy logic-based priority list method to solve the unit commitment problem. The priority list order is selected according to the maximum output power rating of the generating units while satisfying all the constraints over a period of time. The turn on (commitment) and turn off (de-commitment) decision of thermal generating units is handled by priority list order with fuzzy logic algorithm. A fuzzy optimisation-based approach is developed to find the optimal solution by using fuzzy operations and if-then rules. The objective of the optimisation is to achieve minimum operating cost by scheduling of generator units. In solving the unit commitment problem, reliability and feasibility constraints are checked for the planning interval. This method is implemented on standard IEEE 69-bus, 11-thermal generator system. Use of the fuzzy logic controller with priority list method enables the handling of uncertainties in load forecast in an efficient manner.